Effects of an Intensive Lifestyle Intervention to Treat Overweight/Obese Children and Adolescents. (5th June 2017) - Ranucci, Claudia; Pippi, Roberto; Buratta, Livia; Aiello, Cristina; Gianfredi, Vincenza; Piana, Natalia; Reginato, Elisa; Tirimagni, Alberto; Chiodini, Emanuele; Sbroma Tomaro, Emilia; Gili, Alessio; De Feo, Pierpaolo; et al.
Abstract : Objective. The purpose of the present study is to examine the effects of a multidisciplinary lifestyle intervention to treat overweight/obese children and adolescents. The main outcome was cardiometabolic risk based on the waist-to-height ratio (WHTR) measurement. Secondary outcomes were (1 ) changes in body composition; (2 ) adherence to a Mediterranean diet; and (3 ) physical performance. Method. The study involved 74 overweight/obese children or adolescents. The intervention was multidisciplinary including nutrition, exercise, and psychological aspects based on a family-based approach; it was delivered for six months for children and three months for adolescents. Before and after the intervention, several anthropometric measures (height, body weight, body mass index or BMI, waist circumference, and body composition), cardiometabolic risk index (waist-to-height ratio or WHTR), and nutrition habits of the participants and their families were evaluated. In addition, a set of functional motor fitness tests was performed to evaluate physical performance measures. Results. After the intervention both children and adolescents showed a significant reduction in body weight, BMI, waist circumference, fat mass, and WHTR index and an improvement of fat-free mass, adherence to the Mediterranean diet, and physical fitness performance. Conclusion. A family-based multidisciplinary approach is effective in the short term in ameliorating the health status, the nutrition habits, and physical performance in children and adolescents.